O impacto da regulamentação da portabilidade sobre os contratos de crédito imobiliário: uma análise de uma organização financeira - Zanon, Fernando Valério (2017)
The present study analyzed the legislative changes, more precisely, the rules of mortgage portability and its impacts on transactions of a, having the object of analyzing the contracts provided by the financial Institution. The theoretical framework is based on the Transaction Economics Costs, especially those written by Oliver Williamson, and the New Institutional Economy, especially by Douglas North. The analysis focuses on the volume of mortgage operations carried out by the financial institution, before and after the regulation. The data were grouped monthly, comprising the period from 06/2010 to 05/2016. The methodological approach was qualitative and quantitative, and in the first one there is a documentary analysis on the internal regulations of the Financial Institution, the laws (Laws and Resolutions) and the material collected by interviews made with the executives responsible for the creation and implementation of the credit real. The interviews corroborated to demonstrate the lack of opportunistic behavior on the part of the Institution when creating the real estate loan in 2009. In the qualitative analysis, economic indicators were used, besides other information from the operations (value, rate) as independent variable and the contracts were used as the dependent variable, and separated into two groups: before and after the new resolution. The quantitative approach, started by Levene test, was applied to verify if the groups had the same or different variances. The t Test was used to verify if the means belonged to the same population or there were different populations and finally a 4-variable regression analysis was performed (OLS, OLS lagged, GLS lagged and 2-SLS) in order to identify the variables' ability to explain the behavior of the data. The generated econometric model indicated a statistically significant relation between the quantity of contracts and the variable “Resolution”, demonstrating that the impact of the Resolution on operations was negative. Thus, it was possible to analyze that, in spite that the resolution had eliminated the transactions, the mechanisms has brought by transactions reduced transaction costs, as it has brought greater transparency to the process, has improved the symmetry of information and was one of the determining factors for the drastic decrease in volume of portabilities, thus it has allowed banks to make counterproposal to customers (before there was no knowledge of portability by the institution that owned the operation). The resolution has brought significant changes to the institutional environment, calling back to the state the role of regulation and standardization of rules, creating a more transparent, less asymmetric environment and reducing the possibility of opportunistic attitudes.